Taraxacum rhodocarpum and T. schroeterianum (Asteraceae, Crepidinae) are not synonyms, and T. sect. Rhodocarpa is the correct name for T. sect. Alpestria - Štěpánek, Jan; Kirschner, Jan (Phytotaxa, 2022)
Taraxacum schroeterianum Hand.-Mazz. was published to cover distinctive red-fruited slender West Alpine plants with appressed outer phyllaries; it traditionally included T. rhodocarpum Dahlst. as a synonym. A separate section, T. sect. Rhodocarpa van Soest was even erected; its type is T. rhodocarpum on the basis of Art. 10.8 of the ICN. We present a detailed evidence for the separate status of T. schroeterianum and T. rhodocarpum. They differ in a series of morphological features and in the chromosome number. While the former represents a rather isolated taxon, the latter is close to the group of T. reophilum van Soest, the type of T. sect. Alpestria (van Soest) van Soest. Taraxacum sect. Rhodocarpa is therefore considered as the correct name for T. sect. Alpestria. The names T. schroeterianum and T. rhodocarpum are typified, and both these species together with T. sect. Rhodocarpa are supplemented with full descriptions. The name T. sagii Sonck was reassessed and synonymized with T. schroeterianum.